SIMULATION OF DYNAMIC INTERACTION BETWEEN THE BODY OF THE PASSENGER CAR AND TRUCKS - Prykhodko, V. I.; Myamlin, S. V. (Science and Transport Progress, 2008)
The results of mathematical simulation of spatial oscillations of passenger coaches for determination of forces of dynamical interaction of bodies and bogies, which are used in determination of dynamic run and strength characteristics, are presented in this paper.